Evaluation of the diaphragm muscle remodeling, inflammation, oxidative stress and vascularization in smokers: An autopsy study - Nucci, Ricardo Aparecido Baptista (2020)
Background/Aims: Cigarette smoking is a key factor in systemic inflammation and oxidative stress, and it has also been associated with the loss of muscle strength and an elevated risk of pulmonary diseases. Thus, this study aimed to analyze the effects of cigarette smoking on the diaphragm muscle structure of postmortem samples. Methods: Immunohistochemical techniques were used for muscle remodeling (metalloproteinases 2 and 9), inflammation (cyclooxygenase-2), oxidative stress (8-hydroxy-2'-deoxyguanosine), and vascularization (vascular endothelial growth factor). Hematoxylin and eosin stain was used for histopathological analysis and Picrosirius stain was used to highlight the collagen fibers. Results: Cigarette smokers had an increase of diaphragm muscle remodeling, oxidative stress, inflammation, and vascularization compared to non-smokers. Conclusion: Diaphragm muscle structure may be negatively affected by cigarette smoking.